Granulosa cell-derived miR-379-5p regulates macrophage polarization in polycystic ovarian syndrome - Salehi, Reza; Asare-Werehene, Meshach; Wyse, Brandon A.; Abedini, Atefeh; Pan, Bo; Gutsol, Alex; Jahangiri, Sahar; Szaraz, Peter; Burns, Kevin D.; Vanderhyden, Barbara; Li, Julang; Burger, Dylan; et al. (Frontiers in Immunology, 2023)
Polycystic ovarian syndrome (PCOS) is associated with hyperandrogenemia and ovarian antral follicle growth arrest. We have previously demonstrated that androgen-induced exosomal release of miR-379-5p (miR379) from preantral follicle granulosa cells increases the proliferation of target cells via phosphoinositide-dependent kinase 1 (PDK1) upregulation. Androgen also increases inflammatory M1 macrophage abundance, but reduces anti-inflammatory M2 polarization in rat antral and preovulatory follicles. However, the role of small extracellular vesicles (sEVs; also known as exosomes) secretion in determining the cellular content and function of miRNAs in exosome-receiving cells is largely unknown. Our objectives were to determine: 1) the regulatory role of granulosa cells (GC)-derived exosomal miR379 on macrophage polarization and ovarian inflammation; 2) whether miR379-induced M1 polarization regulates GC proliferation; and 3) if this regulated process is follicular stage-specific. Compared with non-PCOS subjects, PCOS subjects had a higher M1/M2 ratio, supporting the concept that PCOS is an inflammatory condition. Ovarian overexpression of miR379 increased the number of M1 macrophages and the M1/M2 ratio in preantral follicles specifically. Transfection of macrophages with a miR379 mimic reduced the cellular content of PDK1 and induced M0M1 polarization; whereas its inhibitor polarized M0M2. Conditioned media from macrophages transfected with miR379 mimic and follicular fluid from PCOS subjects had higher galectin-3 content, a pro-inflammatory cytokine which specifically suppresses human antral follicle GC proliferation. These results indicate that androgen-induced, GC-derived exosomal miR379 increases ovarian inflammation, a condition which suppresses GC proliferation in a follicle stage-dependent manner, as exhibited in PCOS.